2015
DOI: 10.1152/ajpheart.00465.2014
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase inhibition improves coronary endothelial function and prevents the development of cardiac alterations in obese insulin-resistant mice

Abstract: Ouvrard-Pascaud A, Madec A, Richard V, Bellien J. Soluble epoxide hydrolase inhibition improves coronary endothelial function and prevents the development of cardiac alterations in obese insulin-resistant mice. Am J Physiol Heart Circ Physiol 308: H1020 -H1029, 2015. First published February 25, 2015; doi:10.1152/ajpheart.00465.2014.-This study addressed the hypothesis that inhibiting the soluble epoxide hydrolase (sEH)-mediated degradation of epoxy-fatty acids, notably epoxyeicosatrienoic acids, has an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…Therefore, reduced levels of these beneficial LMs, in particular EETs and EDPs, may contribute to the adverse effects of obesity. This is supported by recent studies, which have shown that pharmacological inhibition or transgenic deletion of sEH, which is the dominant enzyme in degrading fatty acid epoxides, protected mice from various adverse consequences of obesity, such as endoplasmic reticulum stress, metabolic syndrome, hepatic steatosis, inflammation, and endothelial dysfunction (11,(14)(15)(16)(17)(18)(19)(20)(21). Together, these results strongly support that CYP-derived fatty acid epoxides play important roles in regulating the pathology of obesity.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, reduced levels of these beneficial LMs, in particular EETs and EDPs, may contribute to the adverse effects of obesity. This is supported by recent studies, which have shown that pharmacological inhibition or transgenic deletion of sEH, which is the dominant enzyme in degrading fatty acid epoxides, protected mice from various adverse consequences of obesity, such as endoplasmic reticulum stress, metabolic syndrome, hepatic steatosis, inflammation, and endothelial dysfunction (11,(14)(15)(16)(17)(18)(19)(20)(21). Together, these results strongly support that CYP-derived fatty acid epoxides play important roles in regulating the pathology of obesity.…”
Section: Discussionsupporting
confidence: 67%
“…HFD feeding also reduced levels of CYP‐derived epoxyeicosatrienoic acids (EETs), which have potent anti‐inflammatory, vasodilative, and cardioprotective effects . Pharmacological inhibition or transgenic deletion of soluble epoxide hydrolase (sEH, the dominant enzyme in degrading EETs) has been shown to protect mice from various adverse effects induced by obesity . Together, these results support that LMs play critical roles in regulating the pathology of obesity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…, Roche et al . ); (iv) upregulation of G protein‐coupled receptor kinase 2 (GRK2) (Taguchi et al . ); (v) overexpression of protein kinase C‐ β (PKC β ) and induction of ET‐1 expression in the endothelium (Lu et al .…”
Section: Nitric Oxidementioning
confidence: 99%
“…Previous studies showed that the tissue levels of COX-derived prostaglandin E 2 (PGE 2 ) and LOX-derived leukotriene B 4 (LTB 4 ) are increased in adipose tissues of obese subjects (15,16). Besides the intensively studied COX and LOX pathways, recent research showed that soluble epoxide hydrolase (sEH), which is the enzyme that converts CYP-produced fatty acid epoxides to the corresponding fatty acid diols, is up-regulated in liver and adipose tissues of obese animals, and could contribute to various obesity-induced disorders (14,(17)(18)(19)(20)(21)(22)(23)(24). However, the roles of eicosanoid signaling in obesity-induced colonic inflammation are unknown.…”
mentioning
confidence: 99%